Lobular Mammary Carcinoma Presenting as an Obstructing Rectal Mass - Ebrahim Almahmeed (Hindawi Limited, 2021)
Breast cancer is the leading cause of cancer death in women, and while metastasis is common to areas like the bone, lungs, and brain, it is rare to metastasize to the gastrointestinal tract and especially to the rectum. Due to the rarity of this condition and its resemblance clinically and radiologically to primary gastrointestinal tract tumors, diagnosis and treatment are challenging. We present a case of metastatic lobular mammary carcinoma in a 52-year-old Bahraini woman who presented with an obstructing rectal mass.